The Effect of Cost Categories and the Origin of their Stickiness on Earnings Forecast: A Comparative Study - Ali Shirzad; Mohamad Javad Saei; Farzaneh Nasirzadeh; Hassan Yazdifar (Iranian Journal of Accounting, Auditing & Finance)
The main aim of this study is to separate the origins of “selling, general, and administrative costs (SG&A)” and “cost of goods sold (COGS)” stickiness and investigate their sources effects on earnings forecast accuracy (EFA). In previous research, various micro and macro factors have been shown to affect asymmetric cost behavior. These factors are rooted in the industry and firm-specific characteristics or specific events, which may occur each year at national or international scales. In this study, a new methodology is presented to separate the cost stickiness sources in the first step, including a novel method for calculating cost stickiness for each firm-year. In the second step, we investigated each firm-year stickiness effect and each stickiness source on the EFA. The study's statistical population consisted of all companies listed on the Tehran Stock Exchange, from which 1080 observations in the 2014-2018 period were selected and reviewed. Our results indicated that EFA has a negative and significant relationship with SG&A andCOGS stickiness, the stickiness of each year, and each company. Still, no significant relationship was found with the stickiness of each industry. Our results demonstrated that the stickiness of SG&A to COGS has a greater effect on the EFA. The findings suggest that each year's events and the intra-organizational events of each company have a greater impact on cost behavior. Hence, managers and financial analysts must consider each source of cost stickiness, especially year-specific events and firm-specific characteristics, and consider their earnings forecast effects to improve their EFA.